Myanmar Agricultural Performance Survey (Monsoon 2023): Farming environment and farm commercialization - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
We have analyzed the farming environment and farm commercialization situation for the 2023 monsoon season from the Myanmar Agriculture Performance Survey (MAPS), conducted at the beginning of 2024. This survey encompassed almost 4,400 crop producers in the monsoon, distributed across all states/regions of the country. Our findings reveal: 1. The security situation in Myanmar continues to pose concerns for farmers, impacting their commercialization practices. During the interview period (January – March 2024): 1.1) 31 percent of farmers reported feeling 'very insecure' or 'insecure'. 1.2) 22 percent expressed serious security concerns while moving around. 1.3) 8 percent stated that conflict in their area prevented the cultivation of some agricultural fields. 1.4) 1.4 percent reported land confiscation as a problem in their community. 1.5) 11 percent indicated fear of storing produce at home due to the risk of confiscation or destruction. 2. Security challenges for farming vary across states and regions, with the Delta area - the country's rice bowl - experiencing relatively better conditions. 3. Limited access to fuel, crucial for irrigation and mechanization among others, poses a significant constraint to farming. Nationally, about a quarter of Burmese farmers reported either no or rare availability of fuel in their communities during the monsoon and post/premonsoon periods. This situation is exacerbated in conflict-affected areas such as Rakhine, Chin, and Kayah, with Rakhine experiencing a dramatic worsening in recent months, with 81 percent of farmers reporting fuel scarcity in the post/pre-monsoon period. 4. Agricultural inputs were generally accessible during the 2023 monsoon season, indicating the resilience of the private sector in delivering these inputs. However, 4 percent of farmers reported unavailability of chemical fertilizers, while 6 percent faced difficulties in accessing mechanization and 18 percent in securing agricultural labor. 5. Input prices increased during the 2023 monsoon compared to the same period in 2022, with mechanized plowing costs rising by 20 percent, and hired labor costs for men and women increasing by 19 percent and 23 percent, respectively. Conversely, urea prices decreased by 15 percent. 6. In the post/pre-monsoon of 2024, wages saw substantial increases compared to the monsoon, especially for men, with a 15 percent rise, possibly linked to the new conscription law. 7. Nearly all crop prices increased compared to the previous monsoon. Paddy prices surged by 64 percent. Conversely, maize prices experienced an 11 percent decrease, likely due to transportation issues via Myawaddy, the border town for trade with Thailand. 8. Most farmers reported higher crop sales income this year compared to the previous one. However, 14 percent of farmers reported lower sales incomes. 9. Farmers in remote and conflict-affected areas face significant disadvantages in farm commercialization. Insecurity and isolation are primarily linked to higher input costs, while output prices are similar or lower compared to secure and well-connected areas. Consequently, farming profitability in these regions is reduced, impacting farmers' income and welfare.